Design of a Compact Ultra-Wideband Bandpass Filter Using Inductively Compensated Parallel-Coupled Lines - Meechai Jamsai (MDPI AG, 2021)
An ultra-wideband bandpass filter (UWB-BPF) using inductively compensated parallel-coupled lines (ICPCL) is presented in this article. It consists of three circuits: a high-pass filter (HPF), a lowpass filter (LPF), and a transmission line. The HPF and the LPF are independently synthesized from the ICPCL. The proposed filter can suppress unwanted frequencies in the upper stopband and increase the skirt slope of the frequency response in the transition bands. The fabricated UWB-BPF with compact size provides good passband performances, with insertion loss of better than −0.49 dB and return loss of better than −12 dB in the frequency range of 2.92–10.95 GHz (the bandwidth of 8.03 GHz). The 107% bandwidth is achieved. In addition, the proposed filter can suppress the spurious frequencies at 2f0, which is greater than 30 dB. The measured results accord well with the simulation results. The novelty of the paper is the introduction of the ICPCL for the construction of the compact UWB-BPF.